Overview of the Implementation of Isolation Precautions, Administrative Controls, COVID-19 Education and Training in the Nursing and Non-Nursing Section at RSI PKU Muhammadiyah Pekajangan Pekalongan - Didik Diyarto; Dyah Putri Aryati (Prosiding University Research Colloquium, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). The transmission of COVID-19 was very fast in various countries, one of it was Indonesia, which eventually became a pandemic. Therefore, it is very important to prevent and control COVID-19 by implementing isolation precautions, administrative control, and conducting education and training. This study aims to describe the implementation of isolation precaution, administrative control, and COVID-19 training education in the nursing an non-nursing section at RSI PKU Muhammadiyah Pekajangan Pekalongan. The sample was 82 respondens, consist of 43 respondents from nursing and 39 respondents from non-nursing. The study used descriptive research design. Observation approach and data collection at the same time (point time approach).The description of the application of isolation precautions in the nursing section applies 31 respondents (72.09%), while non-nursing applies 32 respondents (82.05%). The description of nursing administration control applies 39 respondents (90.70%) while non-nursing applies 33 respondents (84.62%). Overview of education and training in nursing 38 respondents (88.37%) have attended while 35 respondents (89.74%) have attended non-nursing. An overview of the implementation of isolation precaution, administrative control, and COVID-19 training education in the nursing an non-nursing section at RSI PKU Muhammadiyah Pekajangan Pekalongan has implemented well, it is recommended that the PPI Hospital Team carry out education and training on an ongoing basis, as well as improve supervision.